Are dryland strength and power measurements associated with swimming performance? Preliminary results on elite Paralympic swimmers - Cavaggioni, L.; Scurati, R.; Tosin, M.; Vernole, R.; Bonfanti, L.; Trecroci, A.; Formenti, D. (Sports, 2024)
This study aimed to identify the relationship between dryland tests and swimming performance in elite Paralympic swimmers. Fifteen competitive swimmers (age: 27.4 ± 5.4 years, height: 1.70 ± 6.8 m, body mass: 67.9 ± 9.2 kg; 9 males, 6 females) performed a lat pull-down and a bench press incremental load test to determine maximum power (Pmax), the strength corresponding to maximum power (F@Pmax), and the barbell velocity corresponding to maximum power (V@Pmax) from the force-velocity and power-velocity profiles. These outcomes were also normalized by the athlete`s body mass. Swimming performance was carried out from the best result in a 100 m freestyle race registered during an international competition. Lat pull-down F@Pmax was significantly associated with 100 m freestyle chronometric time (Rho = -0.56, p < 0.05), and lat pull-down V@Pmax presented a relationship with mean swimming velocity (Rho = 0.71, p < 0.01). Similarly, bench press F@Pmax and the normalized F@Pmax were significantly related to the mean swimming velocity (Rho = -0.51, Rho = -0.62, p < 0.05). Stepwise multiple regression showed that lat pull-down V@Pmax, bench press normF@Pmax, and V@Pmax accounted for 40.6%, 42.3%, and 65.8% (p < 0.05) of the mean swimming velocity variance. These preliminary results highlighted that simple dryland tests, although with a moderate relationship, are significantly associated with 100 m freestyle swimming performance in elite Paralympic swimmers.